1980
DOI: 10.1021/bi00565a016
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric studies of ligand-induced modulation of calcium adenosine 5'-triphosphatase from sarcoplasmic reticulum

Abstract: The enthalpy change (delta H degrees ') associated with the binding of Mg2+ to the sarcoplasmic reticulum calcium adenosine 5'-triphosphatase [(Ca2+)ATPase] is -76 kcal/mol. The affinity constant for Mg2+ obtained from calorimetric measurements agrees with the Km value for Mg2+ in the phosphorylation of the enzyme by inorganic phosphate (Pi). The delta H degrees ' of binding of Pi to the enzyme is -23.5 kcal/mol, and the affinity constant for Pi obtained from the calorimetry also agrees with the Km value for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
3

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
19
3
Order By: Relevance
“…Thus, binding can be weak when the ligand has in fact a very large effect on the properties of the protein. Very similar numerical data have been reported, for instance, for the binding of Mg 2+ to a Ca 2+ ATPase from sarcoplasmic reticulum (Epstein et al 1980): K298 = 143/M; AH~ = -318 kJ/mol; AS~ = -1025 J/tool 9 K. Such values do not, however, have a general significance. In the reported data for ligand-protein interactions, specific instances can be found for very diverse AH ~ and AS ~ values.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, binding can be weak when the ligand has in fact a very large effect on the properties of the protein. Very similar numerical data have been reported, for instance, for the binding of Mg 2+ to a Ca 2+ ATPase from sarcoplasmic reticulum (Epstein et al 1980): K298 = 143/M; AH~ = -318 kJ/mol; AS~ = -1025 J/tool 9 K. Such values do not, however, have a general significance. In the reported data for ligand-protein interactions, specific instances can be found for very diverse AH ~ and AS ~ values.…”
Section: Discussionsupporting
confidence: 80%
“…The hydrolysis ofATP proceeds with the formation ofa phosphoenzyme (18), and formation of the phosphoenzyme produces a large conformational change. The hydrolysis of the phosphoenzyme is accelerated by Mg2+, and the binding of Mg21 to the enzyme has been extensively studied (19,20 (26). These kinetic results are consistent either with the presence ofan allosteric ATP site or with a single ATP site having different affinities for two conformations of the enzyme (23).…”
Section: Ca'+mg2+-atpasementioning
confidence: 81%
“…The hydrolysis ofATP proceeds with the formation ofa phosphoenzyme (18), and formation of the phosphoenzyme produces a large conformational change. The hydrolysis of the phosphoenzyme is accelerated by Mg2+, and the binding of Mg21 to the enzyme has been extensively studied (19,20). Steady-state kinetics ofATP hydrolysis show apparent negative cooperativity with Hill coefficients of 0.2-0.8, depending on the pH and concentrations of Na+, K+, and Mg2+ (cf.…”
Section: Ca'+mg2+-atpasementioning
confidence: 99%
“…Mechanism I fit the data at pH 6 in 15% Me 2 SO (8) best, and Mechanism IV fit the data at pH 7 in aqueous solution (3) better than any of the other mechanisms. Organic solvent must be more important than pH in the change to Mechanism I (8), because the pH varied from 6 to 7 in the studies of calcium pump in water that concluded Mg 2ϩ and P i bind randomly (3)(4)(5)(6)(7). However, the shift in half-maximum P i concentration with [Mg 2ϩ ] o , predicted by assuming Mg⅐P i is the substrate in organic solvent (Table I, Mechanism I, Row 2), was not observed when phosphorylation data for expressed wildtype Ca-ATPase at pH 6 in 30% Me 2 SO was plotted against [P i ] o in a more recent study (9).…”
Section: Figmentioning
confidence: 99%
“…A recent review article (2) states categorically that Mg 2ϩ and P i bind randomly to Ca-ATPase. Most published studies of purified enzyme in aqueous solution support this interpretation (3)(4)(5)(6)(7). However, a study in an organic solventwater mixture concluded that the true substrate is Mg⅐P i (8), and recently the equation for the half-maximum Mg⅐P i concentration was used to interpret an increased half-maximum P i concentration when the upstream threonine in a signature amino acid sequence for P-type pumps (DKTGT) was changed to serine (9).…”
mentioning
confidence: 91%